Effects of stannous fluoride dentifrice on gingival health and oxidative stress markers: a prospective clinical trial - Niranjan Ramji; Sancai Xie; Ashley Bunger; Rachel Trenner; Hao Ye; Teresa Farmer; Tim Reichling; Julie Ashe; Kimberly Milleman; Jeffery Milleman; Malgorzata Klukowska (BMC, 2024)
Abstract Background Periodontal disease results in oral dysbiosis, increasing plaque virulence and oxidative stress. Stannous fluoride (SnF2) binds lipopolysaccharides to reduce plaque virulence. This study prospectively assessed SnF2 effects on oxidative stress in adults with gingivitis. Methods This was a 2-month, single-center, single-treatment clinical trial. Twenty "disease" (> 20 bleeding sites with ≥ 3 pockets 3 mm-4 mm deep) and 20 "healthy" (≤ 3 bleeding sites with pockets ≤ 2 mm deep) adults were enrolled. All participants were instructed to use SnF2 dentifrice twice daily for 2 months. An oral examination, Modified Gingival Index (MGI) examination and Gingival Bleeding Index (GBI) examination were conducted at baseline, 1 month and 2 months. Gingival crevicular fluid (GCF), saliva, oral lavage and supragingival plaque were collected at each visit to evaluate: Endotoxins, Protein Carbonyls, L-lactate dehydrogenase (LDH), Ferric reducing antioxidant power (FRAP), Oxidized low density lipoproteins (oxi-LDL), IL-6 and C-reactive protein (CRP). A subset-analysis examined participants considered at higher risk of cardiovascular disease. Change-from-baseline analyses within each group were of primary interest. Results The disease group showed statistically significant reductions in GBI at Month 1 (67%) and Month 2 (85%) and in MGI at Month 1 (36%) and Month 2 (51%) versus baseline (p < 0.001). At baseline, the disease group showed greater LDH in GCF and oxi-LDL levels in saliva versus the healthy group (p ≤ 0.01). Total antioxidant capacity (FRAP) in saliva increased versus baseline for the disease group at Months 1 and 2 (p < 0.05), and levels for the disease group were greater than the healthy group at both timepoints (p < 0.05). SnF2 treatment reduced endotoxins (lavage) for both disease and healthy groups at Month 2 (p ≤ 0.021) versus baseline. There was a reduction in oxidative stress markers, namely protein carbonyl in saliva, at Months 1 and 2 (p < 0.001) for both groups and a reduction in cytokine IL-6 (lavage) in the disease group at Month 2 (p = 0.005). A subset analysis of participants at higher coronary disease risk showed reductions in endotoxins in lavage, oxi-LDL, and CRP in saliva at Month 2 (p ≤ 0.04). Conclusion SnF2 dentifrice use reversed gingival inflammation, suppressed endotoxins and reduced some harmful oxidant products in saliva and gingiva. Clinical trial registration Clinicaltrials.gov NCT05326373, registered on 13/04/2022.